A COMPARATIVE STUDY OF DIFFERENT TEACHING STRATEGIES BASED ON TEXT TYPES ON STUDENTSâ SPEAKING COMPETENCY - Nirmala, Tari,; Ni Nyoman, Padmadewi; Luh Putu, Artini, (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This study aimed at comparing the effect of different teaching strategies based on text types on studentsâ speaking competency. Post-test Only Comparison Group Design was applied as the research design. After the treatment sessions, post-test was administered to discover the impact of the treatments. The data obtained from the post-test were analyzed by using descriptive and inferential statistical analyses. Through descriptive analysis, it was found that the mean scores of the two samples for descriptive text were 71.63 and 73.96 and for procedure text were 74.93 and 76.80. The difference between studentsâ speaking competency who were taught using different teaching strategies was analyzed through two-way Anova. Based on the result of the hypothesis testing, it was found that; there was a significant difference between two teaching strategies on studentsâ speaking competency and there was no interactional effect between two teaching strategies and the text types on studentsâ speaking competency. These findings provide empirical evidence of the importance to determine teaching strategies that suit the text types taught in speaking class. Â Â Â Key terms : speaking competency, speaking random club, panauricon and text types